Who loves me best? - Hall, Kirsten; Demarest, Chris L. (Pleasantville, N.Y. : Reader$1 (Bs Digest Children$1 (Bs Books,s, 1999)
A boy$1 (Bs best friend is his puppy.s
Includes gold star reward stickers.
"Preschool-grade 1"--cover.
Keywords: Dogs -- Fiction; Animals -- Infancy -- Fiction; Stories in rhyme